2001
DOI: 10.1112/plms/83.3.743
|View full text |Cite
|
Sign up to set email alerts
|

De Rham Cohomology and Hodge Decomposition For Quantum Groups

Abstract: Let Γ = Γ τ,z be one of the N 2 -dimensional bicovariant first order differential calculi for the quantum groups GL q (N ), SL q (N ),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Proof. Since ·, · is a homomorphism of the left A-modules Γ ⊗ A Γ ∧ and Γ ∧ , it is easy to see that (15) gives a well-defined action of the A-bimodule Γ on Γ ∧ . Hence this action can be extended to an action ⊲ on Γ ∧ of the algebra Γ ⊗ A .…”
Section: Quantum Clifford Algebrasmentioning
confidence: 99%
“…Proof. Since ·, · is a homomorphism of the left A-modules Γ ⊗ A Γ ∧ and Γ ∧ , it is easy to see that (15) gives a well-defined action of the A-bimodule Γ on Γ ∧ . Hence this action can be extended to an action ⊲ on Γ ∧ of the algebra Γ ⊗ A .…”
Section: Quantum Clifford Algebrasmentioning
confidence: 99%
“…Then it is shown that the inclusion map B → X is a fibration as defined earlier (see Theorem 10.5). For the development of noncommutative homogenous spaces the reader should refer to [11,15]. Again the quantum Hopf fibration ι : A (S 2 q ) ֒→ A (SL q (2)) is an example of this situation and we explicitly prove that it is a differentiable fibration for one of two standard four-dimensional bicovariant calculi on A (SL q (2)).…”
Section: Introductionmentioning
confidence: 88%
“…For other results on a Hodge-type decomposition and on de Rham cohomology in the setting of differential calculi over quantum groups, see [3].…”
Section: A Hodge-type Decomposition and The Dirac And Laplace Operatorsmentioning
confidence: 99%